Curriculum and Teaching Strategies for Non-English Speaking Nursery School Children in a Family School - Katz, Lilian G.; Kriegsfeld, Irving; Mission Neighborhood Center, Inc., San Francisco, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1965)
A 3-month study at Mission Neighborhood Family Center and at Telegraph Hill Social Center surveyed questions as related to the experience of these "family schools" with young immigrant families (Central and South American, Caribbean, Chinese, Filipino, French, Irish, Italian, Mexican, Scandinavian, Slavic, Spanish, and Samoan): How can the centers facilitate the children's acquisition of English? How can the centers affect the children's preschool experiences so as to promote elementary school adjustment? What kinds of adaptations in curriculum materials, teaching styles, nursery school designs, and other nursery school procedures would be necessary to realize the foregoing goals? In recognition of the increasing value of bilingual skills and of the fact that foreign language study is now required in California's elementary schools, can the centers develop the child's mother-tongue so as to preserve this head start? Although many relevant data could not be obtained because of time limitation, recommendations are reported in the areas of general facilities, composition of the nursery school group, age grouping, qualifying American children for enrollment, other admission procedures, health requirements, special activities, and professional resources. In general, it is concluded that mixing immigrant children with their English-speaking contemporaries (on a 50-50 basis in groups of no more than 20) seems the most fruitful approach to helping the "family school" children with (1) learning English, (2) elementary school readiness, and (3) problems of acculturation. (JB)
Sponsoring Agency: National Council of Jewish Women, San Francisco, CA. San Francisco Section.
Educational level discussed: Adult Education.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Acculturation; Adult Education; Citations (References); English (Second Language); Family Programs; Immigrants; Minority Groups; Nursery Schools; Preschool Curriculum; Preschool Education; School Readiness; Teaching Methods; California (San Francisco)